Late-time radio observations of the short GRB 200522A: constraints on the magnetar model. Issue 1 (7th May 2021) - Bruni, G; O'Connor, B; Matsumoto, T; Troja, E; Piran, T; Piro, L; Ricci, R
ABSTRACT: GRB 200522A is a short duration gamma-ray burst (GRB) at redshift z = 0.554 characterized by a bright infrared counterpart. A possible, although not unambiguous, interpretation of the observed emission is the onset of a luminous kilonova powered by a rapidly rotating and highly magnetized neutron star, known as magnetar. A bright radio flare, arising from the interaction of the kilonova ejecta with the surrounding medium, is a prediction of this model. Whereas the available data set remains open to multiple interpretations (e.g. afterglow, r-process kilonova, magnetar-powered kilonova), long-term radio monitoring of this burst may be key to discriminate between models. We present our late-time upper limit on the radio emission of GRB 200522A, carried out with the Karl G. Jansky Very Large Array at 288 d after the burst. For kilonova ejecta with energy E ej $≈ 10^{53}\, \rm erg$, as expected for a long-lived magnetar remnant, we can already rule out ejecta masses $M_{\rm ej}\lesssim 0.03\, M_\odot$ for the most likely range of circumburst densities n ≳ 10 −3 cm −3 . Observations on timescales of ≈ 3–10 yr after the merger will probe larger ejecta masses up to M ej ∼ 0.1 M⊙, providing a robust test to the magnetar scenario.